"The Blood‐Dimmed Tide": Witnessing War and Working with the Collective Body in Authentic Movement. (24th September 2015) - Carroll, Roz
Abstract: This article considers how the impact of witnessing war, violence, and news of sexual abuse, as well as processing these themes in clinical work, can be mediated through the practice of Authentic Movement in a group setting. Dramatic movement stories narrate the author's journey into the underworld, and the processing of the visceral impact of violence in the embodiment of the self‐states of victim, bystander, rescuer and perpetrator. Set in a reflexive discussion of the collective body, politics, trauma theory, Aristotle's concepts of catharsis and pity, this article concludes with the acknowledgement that the role of a witnessing community is vital. Copyright © 2015 John Wiley & Sons, Ltd.